Childhood rhabdomyosarcoma: experience of the Children's Solid Tumour Group. - Kingston, J. E. (Nature Publishing Group, 1983)
Seventy three children with rhabdomyosarcoma were treated by members of the Children's Solid Tumour Group during the period, 1974-1981. The extent of disease at diagnosis was found to be the major influence affecting outcome. Children with tumours confined to the tissue of origin with no evidence of nodal or metastatic spread, had a predicted actuarial 5-year survival rate of 86%. However children with 'unconfined' tumours, i.e. those with extension of disease outside the tissue of origin, had a much poorer prognosis with an actuarial 5-year survival rate of only 21%. Two other factors, histological type and site of primary tumour, appeared to affect prognosis but were not independent of the extent of disease at diagnosis. All children were treated according to protocol. Fifty-two patients showed a complete response to initial therapy and 4 of the 11 partial responders achieved a full remission after additional therapy. The overall complete response rate was therefore 77%. Nineteen children who achieved a complete response on initial treatment subsequently relapsed. Only 3 of these children were alive with no evidence of disease 3 years later, a salvage rate of 15%. "Late" relapses, defined as those occurring more than 2 years after diagnosis, were seen in only 5 children, 4 in boys with primary paratesticular tumours.